IMPLEMENTASI PROGRAM USAHA PENINGKATAN PENDAPATAN KELUARGA SEJAHTERA (UUPKS) CAHAYA KAMPUNG TUALANG OLEH DINAS PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK PENGENDALIAN PENDUDUK DAN KELURAGA BERENCANA (DPPPAPPKB) KABUPATEN SIAK TAHUN 2016 - Willy Mulya Putri; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
UPPKS is a group of family planning support activities whose members consist of Prosperous and Prosperous Families I, in order to increase family welfare through entrepreneurial activities. The group initiated by BKKBN in 1976 aims to improve the economic condition of KB family to make life more prosperous. The purpose of this research is to: (1) to know the implementation of UPPKS program implemented by the Office of Women Empowerment, Child Protection, Population Control, And Family Planning (DPPPAPPKB) in increasing family income. (2) To know factors influencing the implementation of program program of UUPKS Cahaya Kampung Tualang by the Office of Women Empowerment of Child Protection of Population Control and Family Planning (DPPPAPPKB). (3) To know the impact that happened with the UPPKS Cahaya Kampung Tualang program for the members of UPPKS group.This study uses qualitative research methods. Data analysis is done by data reduction, data presentation, and conclusion. The subject of this research is DPPPAPPKB Siak Regency, UPPKS Cahaya Kampung Tualang Group.Based on the result of the research, it can be concluded that (1) Implementation of UPPKS Cahaya Kampung Tualang by the Department of Women Empowerment of Child Protection and Family Planning (DPPPAPPKB) of Siak Regency has not run well. This is because of the unfavorable tasks and functions of the Office of Women Empowerment of Child Protection of Family and Family Planning Control (DPPPAPPKB) in the field of Family Planning and Family Welfare in running UPPKS. (2) The increase of the Prosperous Family Stage of UPPKS Cahaya Group is still the status of Prosperous Prosperous Family and Prosperous Prosperous I, which means that the group that has been running for two years has not been able to assist the group members in improving the family economy that is the main goal of UPPKS.Key Words: Implementation, Program, UPPKS, DPPPAPPKB